2022
DOI: 10.1021/acsami.2c04603
|View full text |Cite
|
Sign up to set email alerts
|

Self-Adaptive Dirhodium Complexes in a Metal–Organic Framework for Synthesis of N–H Aziridines

Abstract: Conformational dynamics of active sites in enzymes enable great control over the catalytic process. Herein, we constructed a metal–organic framework with conformationally dynamic active sites (Rh2-ZIF-8). The active sites in Rh2-ZIF-8 were composed of the imidazolate-bridged bimetallic center with a catalytic dirhodium moiety and structural zinc site. Even though the coordination sphere of the dirhodium species was saturated with two circularly arranged esp groups and two axial 2-MeIm ligands, it could still e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…It can be clearly noted that the adsorption property of Rh species in Rh 2 -MOCP-2 accorded with that of Rh 2 (S-Br-NTTL) 4 , which is located around 650 nm. However, Rh 2 -MOCP-1 showed different positions, which located around 600 nm compared to the band of Rh 2 (S-Br-NTTL) 4 and Rh 2 -MOCP-2. This observation suggested that the chemical environment of Rh species in Rh 2 -MOCP-1 was varied from that in Rh 2 -MOCP-2.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It can be clearly noted that the adsorption property of Rh species in Rh 2 -MOCP-2 accorded with that of Rh 2 (S-Br-NTTL) 4 , which is located around 650 nm. However, Rh 2 -MOCP-1 showed different positions, which located around 600 nm compared to the band of Rh 2 (S-Br-NTTL) 4 and Rh 2 -MOCP-2. This observation suggested that the chemical environment of Rh species in Rh 2 -MOCP-1 was varied from that in Rh 2 -MOCP-2.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…23−34 For example, Davies et al 24,25,35,36 reported an efficient and universal approach to immobilize a variety of chiral and achiral dirhodium catalysts cross-linked via axial binding pyridine and rhodium, such as Rh 2 (R-BNP) 4 , Rh 2 (S-PTTL) 4 , Rh 2 (S-DOSP) 4 , and Rh 2 (Oct) 4 . Jones et al 23,27,34 immobilized chiral dirhodium catalysts including Rh 2 (S-DOSP) 4 and Rh 2 (Sp-Br/Ph-TPCP) 4 on silica particles by exchanging one of the bridging ligands in a multiple-step synthesis. Very recently, Buntkowsky et al 28 designed several chiral dirhodium coordination polymers via ligand exchange employing chiral dicarboxylic acids and Rh 2 (TFA) 4 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, an efficient solution is to immobilize homogeneous dirhodium catalysts into/onto heterogeneous support materials. A series of materials have been applied as the host, such as mesoporous silica, crystalline nanocellulose, coordination polymers, metal–organic frameworks (MOFs), and metal–organic cages (MOCs) [ 12 , 13 , 14 , 15 ] Porous materials based on MOCs have received much attention by acting not only as heterogeneous catalysts but also as building blocks of infinite MOFs [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Herein, we employed a metal–organic cage, as we previously reported [ 14 ], to heterogenize dirhodium catalysts by the self-assembly of Rh 2 (OAc) 4 with ditopic carboxylic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of molecular imaging technology, optical probes have attracted much attention relying on the advantages of high sensitivity, non‐invasive speed analysis, and high spatial resolution, and have become a potent tool for real‐time monitoring and imaging of diabetes liver disease. [ 6–14 ] Especially, due to the ability of the near‐infrared (NIR) fluorescence imaging window to detect the light emission of fluorescent dyes in the range of 650 to 900 nm, the spontaneous fluorescence of biological tissues in this range is greatly reduced, and light scattering is reduced. [ 15–25 ] Therefore, the development of near‐infrared fluorescence probes can achieve deeper non‐invasive in vivo imaging and higher spatial resolution.…”
Section: Introductionmentioning
confidence: 99%